Human Liver-Derived Stem Cells Improve Fibrosis and Inflammation Associated with Nonalcoholic Steatohepatitis. (2nd June 2019) - Bruno, Stefania; Herrera Sanchez, Maria Beatriz; Pasquino, Chiara; Tapparo, Marta; Cedrino, Massimo; Tetta, Ciro; Camussi, Giovanni
Abstract : Cell therapy may be regarded as a feasible alternative to whole organ transplantation to treat end-stage liver diseases. Human liver stem cells (HLSCs) are a population of cells easily obtainable and expandable from a human adult liver biopsy. HLSCs share with mesenchymal stromal cells the same phenotype, gene expression profile, and differentiation capabilities. In addition, HLSCs show a specific commitment to the hepatic phenotype. Injection of HLSCs into immunodeficient mice fed with a methionine-choline-deficient diet to induce nonalcoholic steatohepatitis ameliorates liver function and morphology. In particular, HLSC treatment induced a reduction of liver fibrosis and inflammation at morphological and molecular levels. Moreover, HLSCs were able to persist for up to 3 weeks after the injection. In conclusion, HLSCs have healing effects in a model of chronic liver disease.